The role of corporate branding in Serbian mobile phone operator market - Vanka, Gajo (Applied Studies in Agribusiness and Commerce, 2009)
This research is carried out to know the role of corporate branding in mobile phone network along with different influencing factors involved in the purchase of mobile telephone connections. This thesis discusses corporate branding from consumer’s point of view that how much they value it and what type of role it has.